2017
DOI: 10.1080/10942912.2017.1371189
|View full text |Cite
|
Sign up to set email alerts
|

Quality changes of microencapsulated Nigella sativa oil upon accelerated storage

Abstract: Microencapsulation is frequently used to enhance the stability of liquid food by transforming it to a free-flowing powder. This study aimed to evaluate the effect of storage for 24 days at 65°C on the overall quality and stability of microencapsulated Nigella sativa oil (MNSO) compared to uncapsulated Nigella sativa oil (NSO). During storage time, the total oil was extracted from the MNSO and was examined every six days along with the uncapsulated NSO. The uncapsulated oil showed many changes to its properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
(63 reference statements)
1
12
1
Order By: Relevance
“…Rajabi, Ghorbani, Jafari, Mahoonak, and Rajabzadeh (2015) found that there was a decrease in powder moisture content from 5.33 to 2.75% when the total solids content was increased from 30 to 40%, suggesting that solid content casted a positive impact on the powder moisture content. Moreover, Mohammed, Meor Hussin, et al (2017) reported that the microencapsulated oil's moisture content was impacted by increase in the content of total solids as well as the inlet drying temperature. Another study by Mohammed, Tan, Manap, Muhialdin, and Hussin (2019) revealed that microencapsulated NSO by spray drying with combination of MD and SG had moisture content of 3.37% and had reduction after agglomeration process by fluidized bed drying to be 2.27%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajabi, Ghorbani, Jafari, Mahoonak, and Rajabzadeh (2015) found that there was a decrease in powder moisture content from 5.33 to 2.75% when the total solids content was increased from 30 to 40%, suggesting that solid content casted a positive impact on the powder moisture content. Moreover, Mohammed, Meor Hussin, et al (2017) reported that the microencapsulated oil's moisture content was impacted by increase in the content of total solids as well as the inlet drying temperature. Another study by Mohammed, Tan, Manap, Muhialdin, and Hussin (2019) revealed that microencapsulated NSO by spray drying with combination of MD and SG had moisture content of 3.37% and had reduction after agglomeration process by fluidized bed drying to be 2.27%.…”
Section: Resultsmentioning
confidence: 99%
“…In Middle Eastern folk medicine, it has usually been employed traditionally as a natural remedy to treat different diseases for almost 2,000 years (Majeed et al, 2020). N. sativa oil (NSO) is considered as one of the functional oils because it can function as a rich source of natural antioxidants due to the rich content of thymoquinone (Mohammed, Meor Hussin, Tan, Abdul Manap, & Alhelli, 2017). The majority of edible oils are chemically unbalanced and vulnerable to oxidative deterioration, particularly when subjected to light, oxygen, moisture and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The automatic oxidation of NSO could be accelerated by free fatty acids, metals such as iron, monoacylglycerols and diacylglycerols, and thermo-oxidic compounds. Study from Mohammed, Meor Hussin et al (Mohammed et al, 2017a), they pointed out that NSO is susceptible to oxidative degradation and the peroxide value (78.57 ± 0.22 mEq O2/kg oil) of NSO showed significant increases with 24 days. Similar finding was reported by Ramadan et al (Mohamed Fawzy Ramadan and Mörsel, 2004), who reported that NSO showed increasing in the peroxide value up to 64.5 mEq O2/kg after 21 days.…”
Section: Stability Of the Nigella Sativa Oilmentioning
confidence: 98%
“…In addition, encapsulation can also help to overcome the main problems associated with food containing 3 PUFA, the unpalatable “fishy” flavour of fish oil, and the susceptibility of polyunsaturated fatty acids to oxidation, has all of which have a negative impact on food acceptability [ 16 , 22 ]. Encapsulation positively affects the stability and resistance of oils under storage conditions in comparison to oils without encapsulation [ 23 ].…”
Section: Oil Encapsulation Benefitsmentioning
confidence: 99%